Exploring The Impact Of Islamic Branding On @Safiindonesia's Instagram Followers' Beauty Product Purchasing Decisions - Mustofa, Mufid Habib; Munandar, Asep Nur Imam; Maharani, Ananda Putri (CV. ITTC INDONESIA, 2024)
The purpose of this study is to ascertain how followers of Instagram account @safiindonesia are influenced by Islamic branding on cosmetic items when making purchases. The Slovin formula was utilized by the researcher to pick a sample of one hundred individuals. The research data, which were analyzed using SPSS 27.0 for Windows, led to the conclusion that Islamic branding had a major impact on consumer decisions. With a significance level of 0.05, the t-test produced a regression model significance value of 0.000. Consequently, it may be concluded that the Islamic Branding variable (X) has a significant impact on the purchasing choice (Y) when 0.000 < 0.05. The Islamic Branding variable accounts for almost 52% of the variability in followers' purchase decisions, according to the R square value of 0.529.